Determining the authenticity of athlete urine in doping control by DNA analysis. Issue 10 (25th March 2015) - Devesse, Laurence; Syndercombe Court, Denise; Cowan, David
<x xml:space="preserve">Abstract</x> The integrity of urine samples collected from athletes for doping control is essential. The authenticity of samples may be contested, leading to the need for a robust sample identification method. DNA typing using short tandem repeats (STR) can be used for identification purposes, but its application to cellular DNA in urine has so far been limited. Here, a reliable and accurate method is reported for the successful identification of urine samples, using reduced final extraction volumes and the STR multiplex kit, Promega® PowerPlex ESI 17, with capillary electrophoretic characterisation of the alleles. Full DNA profiles were obtained for all samples (n = 20) stored for less than 2 days at 4 °C. The effect of different storage conditions on yield of cellular DNA and probability of obtaining a full profile were also investigated. Storage for 21 days at 4 °C resulted in allelic drop‐out in some samples, but the random match probabilities obtained demonstrate the high power of discrimination achieved through targeting a large number of STRs. The best solution for long‐term storage was centrifugation and removal of supernatant prior to freezing at ‐20 °C. The method is robust enough for incorporation into current anti‐doping protocols, and was successfully applied to 44 athlete samples for anti‐doping testing with 100% concordant typing. Copyright © 2015 John Wiley & Sons, Ltd.